CCAFS science informs updated mitigation commitments for livestock in the Nationally Determined Contributions in Ethiopia and Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
CCAFS, UNIQUE and Ethiopia’s Ministry of Agriculture collaborated to develop new inventory of livestock greenhouse gas (GHG) emissions using Intergovernmental Panel on Climate Change (IPCC) Tier 2 approach which was used to update Ethiopia’s Nationally Determined Contribution (NDC) commitments for livestock GHG mitigation. CCAFS supported Kenya’s State Department for Livestock, increasing its understanding of livestock GHG mitigation options, leading to prioritization of efficient livestock production in Kenya’s updated NDC. Ethiopia and Kenya submitted updated NDCs to UNFCCC in December 2020.